Construction of a probe-immobilized molecularly imprinted electrochemical sensor with dual signal amplification of thiol graphene and gold nanoparticles for selective detection of tebuconazole in vegetable and fruit samples. (1st June 2018) - Qi, Peipei; Wang, Jiao; Wang, Zhiwei; Wang, Xue; Wang, Xiangyun; Xu, Xiahong; Xu, Hao; Di, Shanshan; Zhang, Hu; Wang, Qiang; Wang, Xinquan
Abstract: A probe-immobilized molecularly imprinted electrochemical sensor was constructed for selective determination of tebuconazole in vegetable and fruit samples. Thiol graphene was introduced onto a glassy carbon electrode modified with gold nanoparticles to increase its specific surface area. Prussian blue was co-deposited with gold nanoparticles on the modified electrode and served as the immobilized probe, followed by electro-polymerization of the molecularly imprinted polymer film as the recognition element. Systematic validation and characterization were performed to verify the successful preparation and mechanisms of the Prussian blue and molecularly imprinted polymers in the electrode. Several important parameters, including monomer concentration, scan cycles and pH, were systematically varied to elucidate their influence on the performance of the sensor. Meanwhile, the surface features of the modified electrode were characterized using scanning electron microscopy, atomic force microscopy, cyclic voltammetry and electrochemical impedance spectroscopy. The optimized sensor demonstrated a wide linear range from 5.0 × 10 −8 mol L −1 to 4.0 × 10 −4 mol L −1 with a detection limit of 1.25 × 10 −8 mol L −1 . The proposed sensor exhibited specific recognition of tebuconazole in selectivity experiments and contrast tests. Furthermore, the sensor can be used for detection of tebuconazole in real samples with satisfactory recoveries. Graphical abstract: Image 1 Highlights: A selective and sensitive molecular imprinted electrochemical sensor was developed. Thiol graphene and gold nanoparticles were introduced for signal enhancement. Prussian blue was co-deposited with gold nano-particles as an immobilized probe. Real sample analysis displayed its potential application in tebuconazole detection.